Solusi Al-Qur’an ‎ untuk Kesejahteraan Umat:‎ Infaq Merupakan Soko Guru Perekonomian - Imam Amrusi Jailani (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2010)
Al-Qur’an as the main source of islamic teaching has offered a correct solution for community economic development to create the welfare of the masses. That solution is by optimizing the expenses of wealth for good deed in form of infaq or charity. Universal values which is avalibale in charity imply on the fulfilment of economic justice as well as fair and continuous distribution of wealth. In this sense, charity is perceived as an instrument for economic empowerment for muslim community at large. If this precious value can be accepted by all muslims, economic crisis will not put heavy burden on poor muslims. In fact, it can be a means of poverty alleviation as well. Cahrity also means the value of simple living, avoiding big spendings and being economical. Therefore, it is convenient to attribute charity as social pietism or religious philantropism. Still, charity should be managed in such a way that it can be spent efficiently with great benefit for all muslims. Therefore, managers of charity should be professional.